Realizar una aproximación dendroclimatológica, en un bosque seco utilizando la especie guasmo (guazuma ulmifolia) y su relación con la precipitación y la temperatura en el período 1974 -2007 - Suntaxi, F. (2010)
The aim of this study is to establish the relationship macroclimatic factors (precipitation and temperature) with the formation of growth rings in the species Guasmo (Guazuma ulmifolia) in the farm "San Pedro", Limoncito commune, taking wood samples after leaving a stump of 30 cm tall from the base, a cut cross on the tree, obtaining a section thickness of 5 cm per meter of shaft in ten trees getting a whole series of ring widths, with which genus approximate chronology for this species. Measuring the total number resulted in a correlation of 0.49 to 0.86 with temperature and precipitation, indicating that growth is influenced by environmental stimuli, precipitation is the influential factor in the variability of growth, followed by the temperature and other. This is borne out because there is a wider growth in the rings for the years 1983 and 1998 coinciding with ENSO events (El Niño-Southern Oscillation), which resulted in an increase in precipitation in the coastal region of the Ecuadorian coast and reflection in the ring width Guazuma ulmifolia